ENHANCED THE MECHANICAL PROPERTIES OF WELDING BUTT JOINT OF ALUMINUM ALLOY 6061 BY T6 HEAT TREATMENT PROCESS - Md Ali, M.A.; Yacob, S.; Mohd Ali, N.I.; Abu Bakar, M.H.; Doan, V.A. (Journal of Advanced Manufacturing Technology (JAMT), 2020)
The effect of T6 heat treatment process parameters on the tensile properties of welding butt joint was investigated. T6 heat treatment parameters selected are temperature and time of solution heat treatment (SHT), temperature and time of ageing. Taguchi method and analysis of variance (ANOVA) are used to optimize the heat treatment parameters and to improve the percentage of responses. Aluminum alloy 6061 of dumbbell shape specimen was cut by wire EDM machine followed by T6 heat treatment process. Then the tensile test was conducted to observe the ultimate tensile strength and tensile modulus. From ANOVA, the most affected parameters for ultimate tensile strength and tensile modulus is the temperature of SHT. The value of ultimate tensile strength and tensile modulus obtained for the original welded sample without heat treatment are 89.343 MPa and 17.50 MPa respectively. After heat treatment, the ultimate tensile strength and tensile modulus is increased to 231.964 MPa and 28.57 MPa respectively. It is found that the percentage of ultimate tensile strength and tensile modulus improved up to 8.4 % and 5.09 % respectively. The refinement of grains microstructure after T6 heat treatment process was responsible for enhancement the mechanical properties of welded part.